Diabetes bearer: evaluation of insulin self-application - Tatiane Gomes Guedes; Fernanda Celedonio de Oliveira; Maria Albertina Rocha Diógenes; Cleide Ferreira Damasceno (Rev Rene)
The study aimed at analyzing the self-application of insulin by bearers of diabetes type 2, in a unit of Diabetes and Hypertension reference center, in Fortaleza-CE. It is an exploratory-descriptive study, developed with 80 patients, from January to March, in 2004. The data were collected through semi-structured interviews and analyzed in the computer program Epi-Info 6.0. The results showed that 67 (83.8 %) participants considered the therapy with insulin to be important. As to the technique of application, 30 (37.5 %) do not make the asepsis of the bottle before aspirating and 42 (52.5%) shake the bottle vigorously in order to make the insulin homogeneous. The syringe is re-used by 73 (91.3 %) of the patients. As to the insulin’s storage, 19 (23.8 %) keep it correctly. The turnover of applications is done only by 5 (6.3 %) of the patients. It has been noticed that there are incorrect aspects in the insulin’s usage. A better education in health is proposed, in order to contribute to the selfsufficiency and the enhancement of the Diabetes mellitus bearer’s quality of life.